Community Parenting: The Caring Of The Migrant Workers’ Children In East Java, Indonesia - Asmorowati, Sulikah; Syndi Pitaloka, Dwi Maharani; Wahyuni, Rochyati (Opción, 2019)
This study examines the caring of the children of migrant workers through community parenting, which is one of the pillars of Program Desa Migran Produktif (Desmigratif) or the Productive Migrant Village Program in Pa- ringan Village, Ponorogo. This research used a qualitative approach. This research found that the parenting done through the ParingArt community has impacted positively on the children of the migrant workers in Paringan village. Specifically, the children who join the ‘ParingArt Community’ enjoy a different environment (and a different way of caring) which has led to dif- ferent feelings, attitudes and behaviours. The children are now more focused on positive activities that can encourage them to produce a masterpiece of art, rather than juvenile children who lack a sense of care.